A comparison of critical care transportation modules taught in bachelor's degrees in emergency medical care in South Africa - Conradie, Nathan John (Division of Emergency Medicine, 2020)
The aim of this literature review was to collect and appraise literature related to curricula in critical care transportation and retrieval, pre-hospital care, and aeromedical transportation. The search strategy was twofold. Firstly peer-reviewed published literature was sourced from established platforms. Secondly, grey literature was sourced from internet sources. An assessment of reliability and validity was performed on peer-reviewed literature in the appraisal process. The results of the literature review show that there is a paucity of literature describing critical care modules of pre-hospital educational programmes in South Africa. This lack of literature has led the authors of this review to conclude that there is a potential for insufficient benchmarking and standardisation of the critical care module between universities. The results of this study could allow stakeholders to begin the process of academic standardisation. To provide a comprehensive background on the field of critical care transportation and retrieval and specifically education and training, this literature review starts by describing the field locally. It then attempts to outline the risks associated with critical care retrieval and thereby demonstrating the importance of quality education and regulation that can guide practitioners who perform retrievals. It then seeks to understand the importance of standardsetting within education broadly and the role of curricula in standard-setting. Finally, it provides an overview of methods for comparing curricula. After the background sections, the gathered literature was grouped into themes according to the types of curricula included in the literature. All these types of curricula form part of the critical care transportation and retrieval field, as graduates from these programmes are usually involved in the transportation of critically ill patients between facilities.